Upaya Meningkatkan Keterampilan Praktek Mengajar Melalui Observasi Perencanaan dan Pelaksanaan Kegiatan Pembelajaran Berdasarkan Standar Proses di Kota Mojokerto - Eva Yulianti (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
PPL is the culmination or estuary of the program as well as an arena for forging teacher competencies for prospective teacher students. Through PPL students are given the opportunity to practice applying various theories and professional competencies, skills and insights, attitudes and values â??â??that have been mastered through various subjects, into the real situation. In order for PPL to be optimally useful, PPL is carried out through a conscious and planned, gradual, and systematic coaching process involving many parties, both supervisors, tutors and principals. The purpose of this study is to describe efforts to improve teaching practice skills through observation of planning and implementation of learning activities based on process standards in the City of Mojokerto. This study used action research for three cycles. Each cycle consists of one meeting, each of which consists of four stages: design, activity, and reflection and revision observation. The target of this study is students who practice field experiences in the city of Mojokerto as many as 15 people. Data is obtained in the form of results of filling in planning supervision instruments and teaching activities based on process standards. The conclusions of this study are: Teaching practice skills through observation planning and implementation of learning activities based on process standards in Mojokerto City has increased from the average increase in PPL program participants from 65.87% in the first cycle, to 76.67 & Cycle II and to 82, 86% in Cycle III.